Déficits habitacionais: os limites da interpretação do fenômeno - Forcel, Priscila Kauana Barelli (Universidade Federal de São Carlos, 2025)
Recent estimates indicate that the housing deficit in Brazil exceeds 6 million dwellings, driven by increasing urban population concentration and growing barriers to homeownership. This dissertation analyzes the methodology for calculating the housing deficit developed by the João Pinheiro Foundation (FJP), focusing on its application at the intracity scale. The research acknowledges the institutional relevance of this methodology but questions its conceptual, operational, and political limitations, especially in light of the socio-spatial inequalities that characterize Brazilian cities. The objective is to critically examine the FJP methodology using a qualitative and multiscalar approach, based on secondary data from the 2010 Demographic Census and local surveys conducted in the municipality of Jacareí-SP. The methodological framework includes a review of the housing deficit concept, a theoretical analysis of the FJP methodology, and its practical application to census microdata. The results indicate that the housing deficit is not a neutral absence, but a normative construct that determines who is or is not recognized as a subject of public policy. The analysis revealed limitations in the methodology when applied at the intermunicipal level - particularly through the use of census weighting areas - which obscures internal inequalities and phenomena such as overcrowding, excessive housing cost burden, and inadequate sanitation. The research also incorporated a sociodemographic and infrastructure analysis of deficit households, deepening the diagnostic beyond absolute housing numbers. The limitations encountered - such as the unavailability of 2022 census microdata and the rigidity of official tools - did not compromise the analysis, but rather reinforced the critique of relying solely on census data for urban planning. The study concludes that it is urgent to develop local strategies for housing monitoring based on integrated, multiscalar, and territory-sensitive approaches. This dissertation thus seeks to contribute to the improvement of housing public policies, grounded in fairer, more sensitive, and territorially qualified diagnostics.
Housing deficits: the limits of interpreting the phenomenon
Keywords: Fundação João Pinheiro; Metodologia de cálculo; Políticas públicas habitacionais; Território urbano; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::SERVICOS URBANOS E REGIONAIS::ESTUDOS DA HABITACAO